2021
DOI: 10.1177/00031348211054714
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Time to Surgery in Breast Cancer Patients

Abstract: Background We sought to determine factors affecting time to surgery (TTS) to identify potential modifiable factors to improve timeliness of care. Methods Patients with clinical stage 0-3 breast cancer undergoing partial mastectomy in 2 clinical trials, conducted in ten centers across the US, were analyzed. No preoperative workup was mandated by the study; those receiving neoadjuvant therapy were excluded. Results The median TTS among the 583 patients in this cohort was 34 days (range: 1-289). Patient age, race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Chagpar et al conducted a ten-center analysis to identify factors influencing time to surgery in breast cancer patients. Their study concluded that a preoperative MRI and community practice setting as opposed to academic setting were independent predictors of delayed time to operation [ 41 ]. Additional causes of operative delay included equipment failure, surgeon unavailability, patient clinical condition and availability of instruments [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chagpar et al conducted a ten-center analysis to identify factors influencing time to surgery in breast cancer patients. Their study concluded that a preoperative MRI and community practice setting as opposed to academic setting were independent predictors of delayed time to operation [ 41 ]. Additional causes of operative delay included equipment failure, surgeon unavailability, patient clinical condition and availability of instruments [ 42 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%